2000
DOI: 10.1111/1467-8551.00173
|View full text |Cite
|
Sign up to set email alerts
|

Creative Leadership Processes in Project Team Development: An Alternative to Tuckman's Stage Model

Abstract: Implicit in the project form is the notion that the team structure facilitates the production of a task outcome under non-routine conditions. TheWe propose that theories of project team development and of creativity can be integrated into a new conceptual framework. The framework proposes two structural barriers that bear on team performance, and modifies the well-established team development model of Tuckman. Creative leadership is suggested as an important means of breaching the barriers. Its differentiating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
1
16

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(148 citation statements)
references
References 41 publications
6
125
1
16
Order By: Relevance
“…Creative leaders in the Facilitating context also need to connect the team with various external sources of information and to successfully champion a new idea in the work context Rickards & Moger, 2000). For example, Elkins and Keller (2003) observed that in order to increase the chances of project success in R&D organizations, project leaders must use their networking, political, and persuasion skills in order to secure the support of top management and other divisions inside the organization, and also manage effectively external relationships with clients, suppliers, governments, trade associations, and even competitors.…”
Section: Ethical Leader Behaviorsmentioning
confidence: 99%
“…Creative leaders in the Facilitating context also need to connect the team with various external sources of information and to successfully champion a new idea in the work context Rickards & Moger, 2000). For example, Elkins and Keller (2003) observed that in order to increase the chances of project success in R&D organizations, project leaders must use their networking, political, and persuasion skills in order to secure the support of top management and other divisions inside the organization, and also manage effectively external relationships with clients, suppliers, governments, trade associations, and even competitors.…”
Section: Ethical Leader Behaviorsmentioning
confidence: 99%
“…Trust is defined as the expectation that another individual or group will make good faith effort to behave in accordance with com-mitments, both of explicit or implicit, be honest in whatever negotiations preceded those commitments (Mangundjaya, 2015), deeply connected to successful team performance and has been declared a key component of successful and effective teams (Berry, 2011;Driskell & Salas, 1992), expected to be linked to the evolution of team structures and capable of bridging developmental barriers (Rickards & Moger, 2000), necessary asset for the successful performance of virtual teams (Morita & Burns, 2014), psychological state that exists when you agree to make yourself vulnerable to another (Rousseau et al, 1998), vital collaboration component (Morita & Burns, 2014).…”
Section: Trust In Complexitymentioning
confidence: 99%
“…Benign structures must expand individual and group activities, under the diverse group contingencies (Rickards & Moger, 2000). However, Rickards and Moger believe that there are barriers that block the insertion or development of those benign structures -that emphasize cooperation and mutuality -in the group and, thus, prevent the teams from performing in expected creative ways.…”
Section: The Creative Leadership Modelmentioning
confidence: 99%